2013
DOI: 10.1002/ana.23992
|View full text |Cite
|
Sign up to set email alerts
|

Splicing biomarkers of disease severity in myotonic dystrophy

Abstract: Objective To develop RNA splicing biomarkers of disease severity and therapeutic response in myotonic dystrophy type 1 (DM1) and type 2 (DM2). Methods In a discovery cohort we used microarrays to perform global analysis of alternative splicing in DM1 and DM2. The newly identified splicing changes were combined with previous data to create a panel of 50 putative splicing defects. In a validation cohort of 50 DM1 subjects we measured the strength of ankle dorsiflexion (ADF) and then obtained a needle biopsy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
304
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 216 publications
(333 citation statements)
references
References 47 publications
(145 reference statements)
19
304
1
Order By: Relevance
“…1D). The ΔΨ range in this patient cohort is expected, as myopathic severity (Nakamori et al 2013) and MBNL loss of function (Wagner et al 2016) are also highly variable. Indeed, rank ordering of the adult muscle data sets according to inferred MBNL concentration ([MBNL] inferred ), an approximation of MBNL levels in patient muscle based on a set of 46 validated AS events (Wagner et al 2016), revealed a correlation between functional MBNL level and abnormal MEF2D α 2 exon exclusion (Fig.…”
Section: Severe Rna Misprocessing In Cdmmentioning
confidence: 82%
“…1D). The ΔΨ range in this patient cohort is expected, as myopathic severity (Nakamori et al 2013) and MBNL loss of function (Wagner et al 2016) are also highly variable. Indeed, rank ordering of the adult muscle data sets according to inferred MBNL concentration ([MBNL] inferred ), an approximation of MBNL levels in patient muscle based on a set of 46 validated AS events (Wagner et al 2016), revealed a correlation between functional MBNL level and abnormal MEF2D α 2 exon exclusion (Fig.…”
Section: Severe Rna Misprocessing In Cdmmentioning
confidence: 82%
“…RNAs harboring a long stretch of repeats are thought to fold into stable structures and sequester RNA binding proteins, which, in turn, sets off a molecular cascade leading to neurodegeneration (7). In myotonic dystrophy, sequestration and functional disruption of the muscleblind-like family of RNA binding proteins are associated with specific splicing and expression changes in affected tissues (5,(8)(9)(10)(11)(12).Sequestration of one or more RNA binding proteins into pathological RNA foci has also been proposed in ALS/FTD linked to C9orf72 expansion (1, 13-16). It is anticipated, but has not been demonstrated, that sequestration of RNA binding proteins into expanded GGGGCC RNA foci may lead to major RNA processing alterations as in myotonic dystrophy.…”
mentioning
confidence: 99%
“…RNAs harboring a long stretch of repeats are thought to fold into stable structures and sequester RNA binding proteins, which, in turn, sets off a molecular cascade leading to neurodegeneration (7). In myotonic dystrophy, sequestration and functional disruption of the muscleblind-like family of RNA binding proteins are associated with specific splicing and expression changes in affected tissues (5,(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Their adverse effects are mediated through sequestration of various proteins including the muscleblind-like (MBNL) family of splicing factors. These proteins are functionally depleted by the expanded repeats in DM1 and DM2 which leads to abnormalities in many pathways of RNA metabolism including alternative splicing, a molecular hallmark of DM [4][5][6][7][8] . In DM adult skeletal muscle abnormal expression of embryonic splicing isoforms has been reported for a few hundred genes 4 .…”
Section: Rnamentioning
confidence: 99%
“…These proteins are functionally depleted by the expanded repeats in DM1 and DM2 which leads to abnormalities in many pathways of RNA metabolism including alternative splicing, a molecular hallmark of DM [4][5][6][7][8] . In DM adult skeletal muscle abnormal expression of embryonic splicing isoforms has been reported for a few hundred genes 4 . Given the importance of alternative splicing as one of the biomarkers of disease severity and therapeutic response, accurate quantification of splicing variants could facilitate their refinement for clinical applications.…”
Section: Rnamentioning
confidence: 99%